Characterization of skeletal muscle contraction using a flexible and wearable ultrasonic sensor - Yeung, Elliot; AlMohimeed, Ibrahim; Ono, Yuu (Progress in molecular biology and translational science, 2025)
Monitoring skeletal muscle contraction provides valuable information about the muscle mechanical properties, which can be helpful in various biomedical applications. This chapter presents a single-element flexible and wearable ultrasonic sensor (WUS) developed by our research group and its application for continuously monitoring and characterizing skeletal muscle contraction. The WUS is made from a 110-µm thick polyvinylidene fluoride piezoelectric polymer film. The lightweight and flexible properties of the WUS enable stable attachment to a skin surface without impacting the tissue motion of interest beneath the WUS. As an example of in-vivo demonstrations of muscle contraction monitoring and characterization, continuous monitoring of muscle contraction of the lateral head of the triceps muscle in healthy human subjects is performed using the WUS in the ultrasound pulse-echo technique. The changes in tissue thickness caused by muscle contraction evoked by electromyostimulation (EMS) at different EMS pulse repetition frequencies are measured using an ultrasound time-of-flight method. The muscle contractile parameters are estimated using the muscle twitches obtained at an EMS frequency of 2 Hz, where the muscle can fully relax between consecutive twitches. Furthermore, a level of tetanic progression, where the muscle cannot completely relax, is quantitatively assessed using the fusion index (FI), estimated from the changes in tissue thickness at EMS frequencies ranging from 2 Hz to 30 Hz, with an increment of 2 Hz. It is demonstrated that the unfused and fused tetanus frequencies can be estimated from the FI frequency curve and the contractile parameters obtained at 2 Hz. The WUS and ultrasonic methods demonstrated in this study could be valuable for non-invasive, continuous monitoring of skeletal muscle contractile properties.